Understanding Digital Television - Lundström, Lars-Ingemar (Routledge, 2012)
With the milestones of Digital TV and HDTV, there are lots of questions to be asked about television of today ... Understanding Digital Television explains complex technical systems and solutions in an easy to comprehend manner along with visual 3D graphics. It helps non-technical individuals such as managers, executives, general media professionals, as well as TV and home cinema enthusiasts gain a practical understanding of the equipment, technical aspects of digital television, and various ways of distributing. Most examples are from a European perspective, but also include comparisons with North American systems. This book answers the confusing questions about new devices and digital formats, what to do when the analog TV transmitters are switched off, watching TV using your broadband connection, and much more.